Quality of government accounting and tax information: an extract from Rondônia (Research, Society and Development, 2022)
The present study aimed to analyze the quality of governmental accounting and fiscal information in the State of Rondônia and its municipalities in the Brazilian public sector accounting and fiscal information system (SICONFI) and its relationship with the number of inhabitants and territorial area. An applied research was carried out, using secondary and bibliographic sources, with a qualitative approach, deductive in terms of method and exploratory in terms of purpose. Data collection was carried out on the official website of the National Treasury. Among the results, it was observed that the State of Rondônia occupies the 4th (fourth) place in the ranking of the 27 (twenty-seven) states of the federation, surpassing older states and with a greater population contingent, such as: Rio Grande do Sul, Holy Spirit, among others. Among the best placed municipalities in the state of Rondônia are Santa Luzia d'Oeste, Cerejeiras and Ji-Paraná. In response to the research problem, it was identified that there is no correlation between the quality of the governmental information provided presented in the ranking with the population contingent and the territorial area, such as the state of Rondônia and the municipality of Santa Luzia d'Oeste, which is the 1st (first) in the ranking, despite having a population of only 6,216 (six thousand, two hundred and sixteen inhabitants) and a territorial area of ​​1,197,796 km² (one million, one hundred and ninety-seven thousand, seven hundred and ninety-seven six square kilometers), smaller than many municipalities that obtained worse rankings.